PENGENALAN SAINS MENGGUNAKAN ALAT PERAGA EDUKASI BERBASIS SAMPAH BOTOL PLASTIK - Huda, Didik Nur; Kumala, Siti Ayu; Wahyuni, Sri Endang; Handayani, Santy (LPPM Universitas Nusa Mandiri, 2026)
Kindergarten is an important developmental stage where children learn through play. TKI As Salaam, located in Tapos, Depok, West Java, has 47 students and implements an Islamic-based and child development-oriented learning approach, and has agreed to become a community service partner. The main problem faced by the partner is the limited ability of teachers to introduce science concepts to kindergarten students, both in developing instructional media and in applying appropriate teaching methods. To address this issue, the community service team from Universitas Indraprasta PGRI (Unindra) provided solutions through training, simulation, and mentoring activities focused on developing science teaching aids using plastic bottle waste. The program also included direct science learning activities for students. The results showed a significant improvement in teachers’ competencies, as indicated by an increase in the average pre-test and post-test scores from 73 to 93. Teachers’ responses were highly positive, with scores above 80%. Students also showed very positive responses, with average scores in learning enjoyment (4.86), learning motivation (4.67), clarity of material (4.18), science understanding (4.34), self-confidence (4.77), and expectation for program sustainability (4.80). This program also improved teachers’ skills in creating science teaching aids, particularly water rockets made from recycled plastic bottles. The sustainability of the program is ensured through monitoring and evaluation conducted for up to three months after implementation.